Ethnic housing segregation and the Roma/gypsy population: a Portuguese perspective - Alves, Sónia (AESOP, 2017)
Questions of spatial segregation and over-representation of ethnic minority groups with weak connections to the labour market are central to the political and policy agenda across Europe and academic studies in the fields of housing and urban regeneration. In some countries, the spatial concentration of ethnic minorities is considered in itself an indicator of socio-spatial disadvantage, accentuating pathological discourses related to ethnic communities but in turn providing more resources for these areas. In other countries, where policies have a less preventive character and only intervene during phases of advanced urban decline, the existence of ethnic enclaves and concentrated poverty has led to housing demolition and rehousing, in many cases with controversial results. The relevance of the link between ethnic segregation and integration is known. On the one hand, people create and modify places, on the other hand, spaces in which people live and work affect their social relations, and individual fortunes (eg educational attainment, income levels, reputation). The over-representation of ethnic groups in some areas has been considered a problem where it hinders opportunities of social integration, and when it amplifies processes of stigmatization and the inter-generational transmission of disadvantage. However, it has also been recognized that the concentration of ethnic communities may actually be an advantage for developing relationships of solidarity and the preservation and affirmation of cultural identities. This paper aims to contribute to this debate. It focuses upon the ethnic housing segregation of the Gypsy/ Roma population in Portugal, and asks if ethnic clustering on a number of housing estates is the result of a voluntary impulse towards aggregation (therefore perceived positively by residents), or the result of a lack of choice (thus an ‘institutionalized’ or deliberate political choice to put the Gypsy/Roma people at distance). In the first part, I review the literature on the factors that underlie the social construction of ethnic segregation; in the second part, I review literature that presents the empirical results of research conducted in different locations of Portugal but has in common processes of rehousing of the Gypsy/Roma population in urban areas. I compare these results with those I obtained in field work in Porto where I interviewed Gypsy/Roma people regarding their preferences given models of concentrated housing relocation or more dispersed neighbourhoods. Focusing upon the Portuguese case, I offer some answers to the following research questions: Is the spatial segregation and concentration of the Gypsy/Roma population on a number of housing estates a voluntary choice or a of lack of choice given institutionalized political decisions taken by local authorities or bureaucrats? How does the Gypsy/Roma population feel about segregation and concentration? Do they wish to live in segregated areas, have they been able to choose between more concentrated or dispersed patterns? What are the consequences? Do they believe that spatial segregation reproduces inequality and separation?
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017